'Tangled up in Blue': The Death, Dress and Identity of an Early Viking-Age Female Settler from Ketilsstaðir, Iceland. Issue 1 (2nd January 2019) - SMITH, MICHÈLE HAYEUR; SMITH, KEVIN P; FREI, KARIN M
Abstract : IN 1938, a woman's burial was uncovered by road builders at Ketilsstaðir in north-eastern Iceland. Recently, her physical remains and associated funerary goods were re-examined by an international, interdisciplinary team and formed the basis for an exhibition at the National Museum of Iceland in 2015. This paper focuses on the items of dress that accompanied the woman in order to gain insights into the ways her cultural identity was expressed at the time of her death. Here we explore the roles played by material culture in signaling her identity, and the technologies and trade networks through which she was connected, visually, to Scandinavia, the British Isles, and the Viking world at large.